Criteria to identify old‐growth forests in the Mediterranean: A case study from Sicily based on literature review and some management proposals. Issue 1 (8th March 2018) - Badalamenti, E.; Pasta, S.; La Mantia, T.; La Mela Veca, D. S.
Abstract : Old growth forests are increasingly considered and studied all around the world. However, the knowledge of such important forest systems is still limited in some bioclimatic regions, such as in the Mediterranean Basin. Starting from the knowledge acquired elsewhere, our research was carried out with the aim to select the most effective criteria to identify potential old‐growth forests in Mediterranean ecosystems (Sicily, Italy). Four key proxy indicators were considered: deadwood amount, tree size, structural traits, and tree species richness. A preliminary classification of the local forest stands level in three classes of old‐growthness (high, medium and low) has also been proposed. The main threats to woods conservation, as well as their biological value were considered. Twenty‐one forest stands have been detected and characterized; among them, seven forest stands were close to old growth conditions. Although the selected forest stands are located in protected areas, browsing due to farming and feral ungulates represent a widespread threat. The information provided for each forest stand may represent a starting point for further and in‐depth investigations in similar Mediterranean forest ecosystems.